1996
DOI: 10.1111/j.1476-5381.1996.tb15222.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological effects of monoamine oxidase inhibition on rat midbrain dopaminergic neurones: an in vitro study

Abstract: 1 The effects of the inhibition of monoamine oxidase (MAO) type A and B have been evaluated on the spontaneous firing activity of the dopaminergic (principal) neurones of the rat midbrain intracellularly recorded from a slice preparation. 2 The non-specific MAO inhibitor, pargyline, superfused at a concentration of 10-100 ,uM, decreased or abolished the spontaneous firing discharge of the principal neurones in the subtantia nigra pars compacta and ventral tegmental area. This effect had a slow onset and appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…The finding that dopamine levels are unaltered in the absence of MAO B is in accord with several studies that have used a pharmacological approach to probe the role of MAO B in dopamine neurotransmission (Butcher et al, 1990 ; Kaakkola and Wurtman, 1992 ; Brannan et al, 1995 ; Mercuri et al, 1996). However, increases in dialysate dopamine levels following MAO B inhibition have also been reported (Finberg et al, 1996 ; Lamensdorf et al, 1996).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The finding that dopamine levels are unaltered in the absence of MAO B is in accord with several studies that have used a pharmacological approach to probe the role of MAO B in dopamine neurotransmission (Butcher et al, 1990 ; Kaakkola and Wurtman, 1992 ; Brannan et al, 1995 ; Mercuri et al, 1996). However, increases in dialysate dopamine levels following MAO B inhibition have also been reported (Finberg et al, 1996 ; Lamensdorf et al, 1996).…”
Section: Discussionsupporting
confidence: 82%
“…As dopamine can be catabolized by both MAO A and MAO B, the drug effect on both isoforms could produce the increase in the extracellular level of dopamine. Indeed, consistent with this hypothesis, electrophysiological studies by Mercuri et al (1996, 1997) have shown that the administration of both MAO A and MAO B inhibitors is required for the long‐term prolongation of the dopamineinduced responses in rat midbrain dopaminergic cells.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…All these effects are likely to be independent of nNOS inhibition or more generally of NO production and instead are a consequence of MAO B inhibitory activity possessed by 7-NI. Indeed, it has been shown that the MAO B inhibitor deprenyl decreases the spontaneous firing discharge of DA SNc and VTA cells in vitro [60] and striatal DOPAC [59].…”
Section: No Modulation Of the Activity Of Daergic Nigrostriatal Systemmentioning
confidence: 99%
“…Similarly, Chergui et al (1993) showed that bursting was blocked by the local application (iontophoresis and pressure ejection) of the NMDA receptor antagonist 2-amino-5-phosphonovaleric acid (AP-5) but not by the AMPA/kainate receptor antagonist 6-cyano-7-nitroquinoxalene-2,3-dione (CNQX) (see also Overton and Clark 1997). The duration of the excitatory postsynaptic current (EPSC) evoked by AMPA is ϳ20 ms (Bonci and Malenka 1999), whereas that evoked by NMDA is much longer lasting (Mercuri et al 1996;Overton and Clark 1997), on the order of 600 ms (Destexhe et al 1998). Glutamate affinity for AMPA receptors is lower (EC 50 ϭ 19 M) than for NMDA receptors (EC 50 ϭ 2.3 M) (Patneau and Mayer 1990), thus lower concentrations of glutamate in the cleft are required to activate NMDA receptors, which accounts at least in part for the longer duration of the activation of these receptors.…”
Section: Role Of Different Receptors In the Activation Of Glutamatergmentioning
confidence: 99%